The Study of Sensitivity to Proteolysis of Full-length and Truncated Forms of Recombinant Human Renalase Expressed in the Prokaryotic System - Fedchenko, V.I.; Kaloshin, A.A.; Kaloshina, S.A.; Kopylov, A.T.; Medvedev, A.E. (Biomedical Chemistry: Research and Methods, 2022)
Renalase (RNLS) is a flavoprotein; its N-terminal peptide (amino acid residues 1-17) performs various important functions. Inside cells, it is involved in the Rossmann fold formation (residues 2-35), which is necessary for the binding of the FAD cofactor and the manifestation of the enzymatic activity of RNLS as a FAD-dependent oxidoreductase (EC 1.6.3.5). When RNLS is secreted into the extracellular space, this peptide is cleaved off, and the resulting truncated extracellular RNLS can no longer bind FAD and, therefore, numerous effects described in the literature are carried out by non-catalytic mechanisms. In this work, we have investigated the sensitivity to trypsinolysis of two recombinant forms of human RNLS expressed in prokaryotic cells: (a) full-length RNLS containing the FAD cofactor; (b) a truncated RNLS lacking the 1-17 N-terminal peptide (truncatedRNLS, tRNLS) unable to bind the FAD cofactor. Trypsin (1 unit/20 μL of medium) effectively cleaved both forms of renalase (RNLS and tRNLS). When exposed to a lower concentration of trypsin (0.1 U/20 μL of medium), full length RNLS was more trypsin resistant than tRNLS. We suggest that the different sensitivity of RNLS and tRNLS is apparently determined by the presence of the FAD cofactor in the full-length recombinant protein, which contributes to the formation of a spatial structure that is more resistant to the action of certain proteases.